Cariogenic and erosive potential of pediatric medicines and vitamin supplements - Luciene Souza COUTINHO; Ana Caroline Magalhães Neri SANDE; Natália Novais Vasconcelos NUNES; Rafaela Silva OLIVEIRA; Elisângela de Jesus CAMPOS (Universidade Estadual Paulista, 2022)
Abstract Introduction Pharmaceutical pediatric formulations with low in pH and high in total titratable acidicity used frequently and over long periods of time, have the potential to produce erosive lesions in teeth. On the other hand, high concentration of sucrose, the nocturnal use and the lack of hygiene after its administration, are some factors that can contribute to the cariogenic potential of these formulations. Objective To evaluate in vitro the cariogenic and erosive potential of medicines and liquid vitamins and mineral supplements for pediatric use. Material and method Medicines (n=41) and liquid vitamins and mineral supplements (n=12) childish were selected and analyzed for their physicochemical properties, pH, total titratable acidity (TTA) and total soluble solids concentration (TSS/°Brix). The package inserts and labels were analyzed to identify the composition regarding the content of sugars and acidulants, in addition to the side effects related to salivary flow. Result The pH analysis indicated that there was greater variation in the observed averages in the medication group. As for the TTA at pH 5.5, supplements and medicines groups showed significant variation between the means found (p<0.05). The TTA results at pH 7.0 showed that the highest mean found was in the class of antihistamines and the lowest in the class of drugs that contain the association of antitussives and antihistamines. The analyses TSS demonstrated that across all drug classes and supplements the amount of TSS varied significantly (p<0.05) in all classes of medicines and supplements. Conclusion Most medicines and pediatric liquid vitamin and mineral supplements demonstrated significantly different behaviors within the group itself regarding the variables analyzed that constitute risk factors for the development of dental caries and erosion.